Gambling-related harms attributable to lotteries products. (October 2020) - Booth, Leon; Thomas, Samantha; Moodie, Rob; Peeters, Anna; White, Victoria; Pierce, Hannah; Anderson, Annie S.; Pettigrew, Simone
Highlights: Lotteries products are often viewed as less harmful than other gambling products. Almost a third of respondents who only used lottery products were at-risk gamblers. Younger people, males, e-cig users, and smokers were more likely to be at-risk. Harm-reduction policies aimed at lotteries products may reduce the burden of gambling. Abstract: Lotteries products (lottery tickets and scratch tickets) are the most popular forms of gambling worldwide, however little research has investigated whether these products are associated with gambling-related harm. The limited available research suggests these products are linked to problematic gambling behaviors and a range of resulting negative outcomes, with certain sub-groups appearing to be more vulnerable to experiencing harms. The present study examined risk of gambling-related harm (measured by the Problem Gambling Severity Index) from lotteries products use in an Australian sample of lotteries-only gamblers (n = 540). Additionally, the study investigated whether risk varied according to a range of sociodemographic and behavioral characteristics (age, gender, household income, location (rural vs. metropolitan), employment status, alcohol consumption, smoking status, frequency of e-cigarette use, frequency of scratch ticket use, frequency of lottery ticket use, expenditure on scratch tickets, and expenditure on lottery tickets). Almost one-third of the sample was found to be at some level of gambling-related risk due to their use of lotteries products. Younger respondents, males, current smokers, e-cigarette users, and those who purchase scratch tickets more frequently were more likely to report problematic use of lotteries products. Policy makers should enact strategies to prevent and reduce harms resulting from lotteries products, especially among the identified at-risk groups.